Penciptaan Video Dokumenter â€œDinding-Dinding Cagar Budaya Kota Yogyakartaâ€ - Nugroho, Widhi (Capture : Jurnal Seni Media Rekam, 2011)
Old building representing the indies colony was abandoned in several heritage districtsin Yogyakarta. The Government did not conduct a serious plan and act to conservethe heritage buildings based on the rules of heritage law. The old buildings in Yogyakartahas been mostly over 50th years old, and they have been considered as the heritagebuildings based on the Yogyakartaâ€™s history and the unique architecture. The Governmentand society should be concerned to conserve the heritage buildings in the self ways orcollaborate. This documentary video is one of the efforts of conserving the heritagebuilding in Yogyakarta.